2021
DOI: 10.1002/prp2.761
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial effect behind Cannabis sativa

Abstract: The development of multidrug‐resistant bacteria has revealed the need for new antimicrobial compounds. Cannabis sativa preparations have a long history of medical applications, including the treatment of infectious diseases. This review collects the information about the activity of C. sativa extracts and its main components (cannabinoids and terpenes) against pathogenic bacteria and fungus, to assess its potential using as antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 102 publications
0
27
0
Order By: Relevance
“…Several terpenoids in the Cannabis essential oils have been demonstrated to have anti-microbial effect, which include the monoterpenes α-pinene, linalool, and limonene, and the bitter-tasting sesquiterpenes nerolidol, β-caryophyllene, and caryophyllene oxide [33,[74][75][76]. α-Pinene inhibited the growth of both Gram-positive bacteria (e.g., various Clostridium species, Enterococcus faecium, Streptococcus salivarius, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, Streptococcus pneumoniae) and Gramnegative bacteria (e.g., various Pseudomonas species), as well as the fungus Candida albicans [34,[77][78][79].…”
Section: Anti-microbial Activity Of Terpenoids In Cannabis Essential ...mentioning
confidence: 99%
“…Several terpenoids in the Cannabis essential oils have been demonstrated to have anti-microbial effect, which include the monoterpenes α-pinene, linalool, and limonene, and the bitter-tasting sesquiterpenes nerolidol, β-caryophyllene, and caryophyllene oxide [33,[74][75][76]. α-Pinene inhibited the growth of both Gram-positive bacteria (e.g., various Clostridium species, Enterococcus faecium, Streptococcus salivarius, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, Streptococcus pneumoniae) and Gramnegative bacteria (e.g., various Pseudomonas species), as well as the fungus Candida albicans [34,[77][78][79].…”
Section: Anti-microbial Activity Of Terpenoids In Cannabis Essential ...mentioning
confidence: 99%
“…Wang et al, reported that the activation of cannabinoid receptors reduces inflammation, fibrogenesis, and stimulates reepithelialization during skin wound healing [ 18 ]. Furthermore, there has also been great interest in the antibacterial activity of cannabinoids since 1950 and plenty of works have demonstrated their bacteriostatic and bactericidal effect predominantly against Gram-positive bacteria [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…CBN has shown the potential to have antibacterial activity [31]. CBC has shown to have anti-inflammatory and antinociceptive activity [32]. The common metabolites of Cannabis are shown in Figure 1.…”
Section: Cannabismentioning
confidence: 99%